Predictors and Changes of Self-Perceived Burden Among Stroke Survivors: A 3-Month Follow-Up Study - Wei, Yuanyuan; Ren, Xiaoran; Su, Xiangni; Wang, Xianni; Hua, Yan; Chen, Yu; Shi, Ruijie; Shao, Pei; Lang, Hongjuan; Ni, Chunping (Frontiers in Neurology, 2020)
Background and purpose: Self-perceived burden (SPB) refers to the sense of having become “a burden to others”. Patients’ SPB is associated with distress which has potentially negative influence on disease rehabilitation and quality of life. Stroke represents as significant health and social burden, however there is a lack of evidence about the dynamic changes and predictors of patients’ SPB in the early stage after stroke. Methods: A prospective longitudinal survey study was used. Consecutive stroke inpatients were recruited from the neurology department of three general hospitals in XXX. Patients were surveyed using self-Perceived Burden Scale (SPBS) on the fourth day of admission (Acute phase, Time 1, T1), one month (Time 2, T2) and three months (Time 3, T3) post-stroke. Results: Considerable burden was experienced by 84.15%-91.50% of patients in the first three months post-stroke. The mean score of physical burden was highest. Over time, physical, emotional, and economic burden all declined. The following characteristics had significant association with patient greater SPB at T1, T2 and T3: age, self-evaluated economic pressure, co-occurring chronic diseases, and functional status (P<0.01).Patients’ knowledge about disease was only significantly associated with SPB at T3(P<0.01). Conclusions: Patients experienced a higher degree of self-perceived burden in the early stage after stroke. Addressing the characteristics and predicting factors as well as the development of a targeted intervention for self-perceived burden will go a long way in improving survival and reducing post-stroke disability.